Light rail transit and housing markets in Charlotte-Mecklenburg County, North Carolina: Announcement and operations effects using quasi-experimental methods. (April 2019) - Ke, Yue; Gkritza, Konstantina
Abstract: As planners and engineers in large cities around the United States continue to seek solutions to transportation-related problems such as congestion, greenhouse gas emissions, and safe and efficient access to goods and services, light rail transit (LRT) systems have become an increasingly popular option. While LRT has the potential to address these issues, it also has the potential to create negative externalities. This study examines the effects that LRT has had on the single-family residence housing market in Charlotte-Mecklenburg, North Carolina, in both the announcement and operations phases. Using spatially explicit quasi-experimental econometric models, we found that the announcement of the LRT led to increases in price per square feet for properties as distance to LRT station decreases while the price per square foot of properties decreases as distance to LRT station decreases after the system began operations. These results indicate that while land speculation may have resulted from the announcement of the LRT system, homeowners living closest to the stations during operations may have viewed the LRT stations more as a nuisance than a benefit.